2011
DOI: 10.1080/17533011003631469
|View full text |Cite
|
Sign up to set email alerts
|

This is the embodiment of empowerment: use of forum theatre to address tobacco use in community psychiatry

Abstract: Involvement in theatre has become an accessible avenue for individuals within the psychiatric system to dispel myths which surround their lived experiences and to actively create representations of themselves. Since practicing effective research knowledge translation to address tobacco within the context of mental health is emotionally charged, it must be approached not only with care and attention but also with creativity and skill. Interactive or "Forum" Theatre is a powerful tool to address sources of oppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Forum theatre has been used elsewhere in multiple contexts: as a way of understanding possible treatments in mental health (Malchy, Johnson, & McBride, 2011) as a form for training simulation in nursing (Tuxbury, Wall McCauley, & Lement, 2012) as a way to train health care professionals in communication (Middlewick, Kettle, & Wilson, 2012), in community conflict resolution in Costa Rica (Hawkins & Georgakopolous, 2010); as a way of exploring HIV and AIDS issues in the workplace (Durden & Nduhura, 2011); in aboriginal health research (Linds et al, 2013) and renewal of health care in Finland (Pässilä, Oikarinen, Parjanen, & Harmaakorpi, 2013). It is a means for the audience and the actors to engage in problem solving and to develop a sense of competency (Dalrymple, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Forum theatre has been used elsewhere in multiple contexts: as a way of understanding possible treatments in mental health (Malchy, Johnson, & McBride, 2011) as a form for training simulation in nursing (Tuxbury, Wall McCauley, & Lement, 2012) as a way to train health care professionals in communication (Middlewick, Kettle, & Wilson, 2012), in community conflict resolution in Costa Rica (Hawkins & Georgakopolous, 2010); as a way of exploring HIV and AIDS issues in the workplace (Durden & Nduhura, 2011); in aboriginal health research (Linds et al, 2013) and renewal of health care in Finland (Pässilä, Oikarinen, Parjanen, & Harmaakorpi, 2013). It is a means for the audience and the actors to engage in problem solving and to develop a sense of competency (Dalrymple, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The desire to raise awareness about a research topic and research findings [9,[13][14][15][16][17][18][19]24,[31][32][33][34][35]36,INT5,INT6] or to mobilise change in behaviours in specific stakeholder groups or at the policy level are particularly frequent aims [9,[20][21][22][23][24]26]. Raising awareness may include increased awareness about the empirical evidence on a specific topic [13, 14, 16-18, 31-34, 37, 38].…”
Section: What Does the Use Of Artsbased Engagement Approaches Seek To...mentioning
confidence: 99%
“…Raising awareness may include increased awareness about the empirical evidence on a specific topic [13, 14, 16-18, 31-34, 37, 38]. However, it can also include creating spaces for engagement, debate and dialogue around the research topic [9,13,24,32,35,36,INT6] or raising the profile of a research study, programme or institution [14].…”
Section: What Does the Use Of Artsbased Engagement Approaches Seek To...mentioning
confidence: 99%
“…Participation in drama projects has also been associated with enhanced self-esteem, self-knowledge, relaxation, connection with others and empathy (Moran and Alon, 2011). Furthermore, there is preliminary evidence that, through drama, both players and audience members are activated to reflect on their attitudes and behaviours (Malchy et al , 2011; Stephens-Hernandez et al , 2007). The effects of drama education on (forensic) psychiatric patients are studied less frequently.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on a drama project involving psychiatric patients and their treatment providers as the cast, it was found that the participants had a meaningful group experience: the group was experienced as a safe place, providing social support and decreasing power differences between patients and staff. Participants reported that working with the “other” made a positive emotional impact (Malchy et al , 2011). Positive effects of drama education are not only reported for psychiatric patients but also for their staff.…”
Section: Introductionmentioning
confidence: 99%